Efficacy and Safety of Mitoxantrone Hydrochloride Injection for Tracing Axillary Sentinel Nodes in Breast Cancer: A Self-Controlled Clinical Trial - Jiao, Dechuang; Yang, Benlong; Chen, Jiajian; Wang, Chunjian; Jin, Lidan; Zhao, Wenhe; Gao, Xueqiang; Wang, Haibo; Li, Jun; Zhao, Haidong; Wu, Di; Fan, Zhimin; et al. (Frontiers in Oncology, 2022)
Background: Mitoxantrone hydrochloride injection for tracing (MHI), a new strategy to identify lymph nodes, has not been tested for axillary node staging in breast cancer. This multicenter, self-controlled, non-inferiority trial aimed to evaluate MHI’s efficacy and safety in sentinel lymph node biopsy (SLNB). Methods: The trial was conducted across 7 hospitals from December 2019 to December 2020. Patients with early-stage breast cancer received MHI and technetium-99m (99mTc) during the surgery. Sentinel node detection rates were compared between MHI and 99mTc to evaluate non-inferiority and concordance. Non-inferiority was valid if the lower limit of the 95% CI of sentinel node relative detection rate difference was ≥ -5%. Results: SLN relative detection rate of MHI was 97.31% (362/372). Seventy nine point six nine percent（871 /1093）of the SLNs were co-detected by both tracers. Four point one three percent（16/387）of the patients had adverse events and recovered during the follow-up. Conclusions: MHI is a lymphatic tracer with comparable efficacy to radionuclides and can be used alone or in combination with radioactive substances for SLNB.